How Knowledge Mapping Can Bridge the Communication Gap Between Caregivers and Health Professionals Supporting Individuals With Complex Medical Needs: A Study in Fragile X Syndrome - Kelm, Karen; Bolduc, Francois V. (Frontiers in Psychiatry, 2021)
The challenges of caring for children with medical complexities, such as Fragile X syndrome (FXS), are multiple and felt by both parents and healthcare providers. Children and adults with FXS, like most individuals with neurodevelopmental disability, experience a wide range of symptoms and require more than regular care. This creates needs for parents and several health and education professionals to collaborate effectively. Here we review issues with communication, as well as potential strategies developed in other cases of complex medical needs which we could apply to FXS. First, we begin by illustrating the communication challenges parents and health care providers face when caring for a child with FXS. We explore three key components impacting communication quality: 1) health literacy, 2) mental models, and 3) knowledge transfer. Next, we scope the literature for tools available to address parents' and health care providers' unmet communication needs during the care coordination process. We focus on mapping as a potential tool to enhance communication in the care of individuals with FXS. Altogether, our review identifies several gaps in knowledge of FXS regarding communication models, which underlines the need to better understand differential mind models, and points toward an achievable approach to improving patient-centered care. Finally, we show why parents and health care providers need to be provided with tools to aid in quality communication and discuss how technology can facilitate quality information exchange.